2021
DOI: 10.1088/2053-1591/abd73b
|View full text |Cite
|
Sign up to set email alerts
|

Structural and electrical properties of La3+ ions substituted MnFe2O4 ferrite nanoparticles synthesized via cost-effective reverse micelles strategy

Abstract: La3+ ions substituted manganese ferrite (MnFe2-x La x O4) nanoparticles via reverse micelles strategy were synthesized and their structural and electrical properties are discussed in this article. Using low-cost precursors, mono-dispersed, and well crystalline MnFe2-x La x O4 nanoparticles were prepared at low temperature. X-ray diffraction (XRD) explored cubic spinel structure with minute secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The secondary orthoferrite phase formation in ferrites is observed by other researchers once the solubility limit of rare Earth ions exceeds. [37][38][39] Figure 6 shows the FESEM patterns of all Dy 3+ substituted Ni-Zn synthesized powders and it is observed that the prepared powders have shown spherical morphology with some agglomeration. The particle size was measured using linear intercept by taking the average of three different places and the obtained values are depicted in Table II.…”
Section: Resultsmentioning
confidence: 99%
“…The secondary orthoferrite phase formation in ferrites is observed by other researchers once the solubility limit of rare Earth ions exceeds. [37][38][39] Figure 6 shows the FESEM patterns of all Dy 3+ substituted Ni-Zn synthesized powders and it is observed that the prepared powders have shown spherical morphology with some agglomeration. The particle size was measured using linear intercept by taking the average of three different places and the obtained values are depicted in Table II.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is important to make a good selection of the appropriate synthesis method according to the desired properties and applications. Various methods have been used for the synthesis of ferrite nanoparticles, such as: coprecipitation [14], sol-gel [15], autocombustion [16], hydrothermal synthesis [17], microemulsion [18], reverse micelles [19]. Chemical coprecipitation has proven to be a simple, fast, and low-cost synthesis method that allows obtaining nanoparticulate powders [20].…”
Section: Introductionmentioning
confidence: 99%